Allostatic load in the association of depressive symptoms with incident coronary heart disease: The Jackson Heart Study. (November 2019) - Gillespie, Shannon L.; Anderson, Cindy M.; Zhao, Songzhu; Tan, Yubo; Kline, David; Brock, Guy; Odei, James; O'Brien, Emily; Sims, Mario; Lazarus, Sophie A.; Hood, Darryl B.; Williams, Karen Patricia; et al.
Highlights: African Americans are at heightened risk for coronary heart disease. Biologic pathways are poorly understood. In this study, depressive symptoms were associated with allostatic load in females. Depressive symptoms and allostatic load predicted incident coronary heart disease. Metabolic allostatic load was a partial mediator in the pathway among females. Abstract: African Americans are at heightened risk for coronary heart disease (CHD), with biologic pathways poorly understood. We examined the role of allostatic load (AL) in the association of depressive symptoms with incident CHD among 2, 670 African American men and women in the prospective Jackson Heart Study. Depressive symptoms were quantified using the Center for Epidemiologic Studies Depression Scale (CES-D). Incident CHD was ascertained by self-report, death certificate survey, and adjudicated medical record surveillance. Baseline AL was quantified using biologic parameters of metabolic, cardiovascular, immune, and neuroendocrine subsystems and as a combined meta-factor. Sequential models adjusted for demographic, socioeconomic, and behavioral covariates, stratified to examine differences by sex. Greater depressive symptomatology was associated with greater metabolic, cardiovascular, and immune AL ( p -values≤0.036) and AL meta-factor z-scores ( p  = 0.007), with findings driven by observations among females. Each 1-point increase in baseline depressive symptomatology, and 1-SD increase in metabolic AL, neuroendocrine AL, and AL meta-factor z-scores was associated with 3.3%, 88%, 39%, and 130% increases in CHD risk, respectively ( p- values <0.001). Neuroendocrine AL and AL meta-factor scores predicted incident CHD among males but not females in stratified analyses. Metabolic AL partially mediated the association of depressive symptoms with incident CHD (5.79% mediation, p  = 0.044), a finding present among females ( p  = 0.016) but not males ( p  = 0.840). Among African American adults, we present novel findings of an association between depressive symptomatology and incident CHD, partially mediated by metabolic AL. These findings appear to be unique to females, an important consideration in the design of targeted interventions for CHD prevention.